2008
DOI: 10.1111/j.1099-0860.2008.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Forms of Child Labour in Turkey

Abstract: Two little known forms of child labour in Turkey are examined. The process through which these children are made to work has parallels with the experiences of slaves. First, a long‐standing practice from Northwestern Turkey of parents hiring children to better‐off farmers is examined. Further, a more recent problem is examined where children are trafficked to big cities and forced to join criminal rings. Both forms of child labour are consequences of poverty. The factors that give rise to child trafficking and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…National Crime Agency 2015; National Criminal Police 2007; National Police Board 2009, 2010, 2011, 2012; Serious Organised Crime Agency 2011). Numerous publications were, however, explicitly framed as research yet lacked the basic characteristics of scientific enquiry; examples with academic authors included Degirmencioglu et al (2008), Oude Breuil (2008), Pearce et al (2009) and Ryazantsev et al (2015). Such issues were also found in reports from official agencies.…”
Section: Resultsmentioning
confidence: 99%
“…National Crime Agency 2015; National Criminal Police 2007; National Police Board 2009, 2010, 2011, 2012; Serious Organised Crime Agency 2011). Numerous publications were, however, explicitly framed as research yet lacked the basic characteristics of scientific enquiry; examples with academic authors included Degirmencioglu et al (2008), Oude Breuil (2008), Pearce et al (2009) and Ryazantsev et al (2015). Such issues were also found in reports from official agencies.…”
Section: Resultsmentioning
confidence: 99%
“…(2) Item development: In this step, similar inventories related to child abuse were examined. For this phase we used relevant resources for each dimension (Degirmencioglu et al, 2008; Ferguson, 2005; Galea, 2008; Gharaibeh & Hoeman, 2003; Guarcello et al, 2010; Rahbari, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The research team evaluated the theoretical sources related to child labour and child abuse. The study and evaluation of the tools used in previous studies (Bourdillon & Carothers, 2019; Degirmencioglu et al, 2008; Gamlin et al, 2015; Gharaibeh & Hoeman, 2003; Guarcello et al, 2010; Ibrahim et al, 2019; Myers, 1999; Nieuwenhuys, 2007; Öncü et al, 2013; Roggero et al, 2007; Shabbir et al, 2020; Thévenon & Edmonds, 2019; Woodhead, 1999) showed that although tools have been used to monitor and guide efforts towards the progressive elimination of child labour, most of these tools have been developed using a similar approach and were based on existing knowledge. Although these studies have measured child labour in similar ways through surveys, estimates of child labour vary significantly across different kinds of surveys.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Engaging in child labor is considered an acceptable pathway to prepare children to be hardworking adults, and resilient to future work challenges [ 19 ]. Children in Turkey are found to work during their early years in order to contribute to family farm work [ 36 ]. Inherent in these justifications of child labor and child work are normative interpretations of the values of hard work, resilience, success, and achievement.…”
Section: Introductionmentioning
confidence: 99%